Comparative analysis of EEG in patients with schizophrenia receiving various atypical antipsychotics - S. A. Galkin; E. G. Kornetova; S. A. Ivanova (Бюллетень сибирской медицины)
Aim. To conduct a comprehensive analysis of EEG recordings of schizophrenia patients receiving atypical antipsychotics as monotherapy.Materials and methods. We examined 94 patients with schizophrenia aged 33 [28; 40] years with a disease duration of 10 [4; 15] years. The patients were divided into 5 groups depending on the antipsychotic drugs they took: 1) risperidone – 31 patients; 2) quetiapine – 20 patients; 3) aripiprazole – 11 patients; 4) olanzapine – 13 patients; 5) clozapine – 19 patients. EEG was recorded during wakefulness with closed eyes (background test), 3-minute hyperventilation, and rhythmic photostimulation in all patients. To describe and interpret the received recordings, the EEG classification according to J. Micoulaud – Franchi et al. was used.Results. EEG modifications (score > 1A) were observed in 61.7% (n = 58) of patients. In the group of patients receiving risperidone, EEG modifications were found in 48.4% of cases, in patients taking quetiapine – in 70% of cases, aripiprazole – in 63.6% of cases, olanzapine – in 61.5% of cases, clozapine – in 73.7% of cases. The frequency of epileptiform patterns in patients receiving olanzapine was significantly higher than in those taking risperidone (p = 0.033) and clozapine (p = 0.032). Slowing in the EEG (score > 1) was more often observed in patients taking clozapine – 63.2% (n = 12), olanzapine – 61.5% (n = 8), and quetiapine – 60% (n = 12). Slower EEG waves were less common in patients receiving aripiprazole – 45.5% (n = 5) and risperidone – 45.2% (n = 14). In the group of patients with EEG slowing (score > 1), the dose of chlorpromazine equivalent was significantly greater compared to patients with normal EEG (p = 0.00046).Conclusion. The data obtained demonstrate changes in EEG parameters during monotherapy with atypical antipsychotics and indicate their dose-dependent effect on the bioelectrical activity of the brain.